THE ROLE OF LISTENING IN DEVELOPING PRONUNCIATION AND FLUENCY - Matqurbonova Ro’zaxon Zokirjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Listening plays a fundamental role in the development of accurate pronunciation and fluency in language learning. This article explores how exposure to native speech models, intonation, stress patterns, and real-time listening practice contribute to enhancing learners’ speaking abilities. Techniques such as mimicry and shadowing are highlighted as effective methods for improving both pronunciation and fluency. Furthermore, the importance of phonological awareness and listening to varied accents is discussed as key factors that help learners internalize the natural rhythm and flow of the language. Ultimately, this article demonstrates that listening is a vital component in building strong communication skills, as it lays the foundation for producing clear and fluent speech.